Implementasi Kebijakan Pengarusutamaan Gender Dalam Pembangunan di Kota Sukabumi - Rahminigrum, Anita; Rachmawati, Ike (JPM MOCCI : Jurnal Pengabdian Masyarakat Ekonomi, Sosial Sains dan Sosial Humaniora, Koperasi, dan Kewirausahaan, 2024)
The fourth Anugerah Parahita Ekapraya (APE) award in 2020 from the Ministry of Women's Empowerment and Child Protection is proof of Sukabumi City's achievements in implementing development that ensures gender equality and justice. The Gender Empowerment Index (IDG) and Gender Development Index (IPG) as macro statistical indicators used to measure gender development show that there is still a gap in gender development, but conditions are improving throughout the 2018-2022 period. Gender Mainstreaming (PUG) is a strategy launched by the government to ensure justice for men and women in gaining access, participation, control and development benefits. The implementation of PUG policy in development in Sukabumi City has been outlined in legal regulations containing the subject person in charge of the program and the PUG development implementation plan for the 2018-2023 period. This paper aims to review the implementation of PUG policies in Sukabumi City that have been carried out using Van Metter and Van Horn policy implementation model analysis tools with literature review research methods. The results showed that the implementation of PUG policy in Sukabumi City has gone quite well due to the support of parties related to PUG, government officials, and supporting facilities and infrastructure that are driving factors. Meanwhile, the inhibiting factor in the implementation of PUG policy is the strong stigma of the people of Sukabumi City regarding gender assumptions in everyday life.